Formation of a silicon terminated (100) diamond surface - Schenk, A.; Tadich, A.; Sear, M.; O'Donnell, Kane; Ley, L.; Stacey, A.; Pakes, C. (American Institute of Physics Inc., 2015)
We report the preparation of an ordered silicon terminated diamond (100) surface with a two domain 3×1 reconstruction as determined by low energy electron diffraction. Based on the dimensions of the surface unit cell and on chemical information provided by core level photoemission spectra, a model for the structure is proposed. The termination should provide a homogeneous, nuclear, and electron spin-free surface for the development of future near-surface diamond quantum device architectures.